Do Term Limits Restrain State Fiscal Policy? Approaches for Causal Inference in Assessing the Effects of Legislative Institutions. Issue 3 (18th July 2013) - Keele, Luke; Malhotra, Neil; McCubbins, Colin H.
Abstract : Scholars of state politics are often interested in the causal effects of legislative institutions on policy outcomes. For example, during the 1990s a number of states adopted term limits for state legislators. Advocates of term limits argued that this institutional reform would alter state policy in a number of ways, including limiting state expenditures. We highlight a number of research design issues that complicate attempts to estimate the effect of institutions on state outcomes by addressing the question of term limits and spending. In particular, we focus on (1) treatment effect heterogeneity and (2) the suitability of nonterm‐limit states as good counterfactuals for term‐limit states. We compare two different identification strategies to deal with these issues: differences‐in‐differences (DID) estimation and conditioning on prior outcomes with an emphasis on synthetic case control. Using more rigorous methods of causal inference, we find little evidence that term limits affect state spending. Our analysis and results are informative for researchers seeking to assess the causal effects of state‐level institutions.